Compulsive gaming in secondary school students from five peruvian cities: Usage and addiction to the Pokémon GO game. - Mejia, C.R (2019)
Introduction: Some years ago, the Pokémon GO game became incredibly popular. However, no studies on the subject have been conducted in Peru involving vulnerable populations, such as adolescents. Objective: To determine if the number of hours playing the Pokémon GO game is associated with Internet and/or video game addiction, as well as to other factors in secondary school students from five Peruvian cities. Materials and methods: Cross-sectional, analytical, and multi-centric study, with a sample of 944 school students. General characteristics, including socio-educational aspects, and Internet and/or video game addiction were analyzed, as well as variables related to the use of the game, such as problems at home, with teachers, accidents, and theft. Results: We found statistical associations between the assessed variables and increased playing time. 409 (44%) students had an Internet addiction, 215 (23%) were addicted to video games, and 336 (49%) spent a significant number of hours per day playing Pokémon GO. A greater number of hours playing Pokémon GO was associated with having a video game addiction (prevalence ratio (PR): 1,33; 95% confidence interval (CI): 1.07-1.65), greater use of cell phone applications (PR: 1.02; 95% CI: 1.01-1.03), reprimand by parents (PR: 1.09; 95% CI: 1.02-1.18), and reprimand for arriving late to class (PR: 1.44; 95% CI: 1.07-1.18). On the other hand, students who played a greater number of video games used Pokémon GO by a lower number of hours (PR: 0,98; 95% CI: 0.97-0.99), adjusted by the respondent´s location. Conclusion: Higher usage levels of Pokémon GO were associated with having a video game addiction, greater use of phone applications, negative repercussions from parents, and reprimand for arriving late to class.